Double-mode model about distributions of network traffic - CHEN Ming; PEI Ling-bo; LIANG Wen (Tongxin xuebao)
Three propositions about distribution of network traffic were put forward and analyzed. The shaping process of the high bandwidth-low bandwidth-high bandwidth network structures which are prevalent in Internet was pointed out and then the novel concept of shaping operator was proposed. The forming mechanism of Poisson distribution for sub-second time scales on major backbone link was analyzed and a double-mode transition model between self-similarity distribution and Poisson distribution was put forward. Finally,the validity of the double-mode transition model was veri-fied by simulation experiments. The research results give a universal explain about current traffic distributions and have important effects on many research fields such as design of network structure,congestion control mechanism,admission control and QoS.